Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Explore our Q&A platform to find in-depth answers from a wide range of experts in different fields. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.

How do i derive (x^-4) using the limit definition [f(x+h) - f(x) / h]

Sagot :

[tex]f'(x)=\lim\limits_{h\to0}\frac{f(x-h)-f(x)}{h}\\\\f(x)=x^{-4}=\frac{1}{x^4}\\\\f'(x)=\lim\limits_{h\to0}\frac{(x+h)^{-4}-x^{-4}}{h}=\lim\limits_{h\to0}\frac{\frac{1}{(x+h)^4}-\frac{1}{x^4}}{h}=\lim\limits_{h\to0}\frac{\frac{x^4-(x+h)^4}{x^4(x+h)^4}}{h}\\\\=\lim\limits_{h\to0}\left[\frac{x^4-x^4-4x^3h-6x^2h^2-4xh^3-h^4}{x^4(x+h)^4}\cdot\frac{1}{h}\right]=\lim\limits_{h\to0}\frac{-4x^3h-6x^2h^2-4xh^3-h^4}{hx^4(x+h)^4}[/tex]

[tex]=\lim\limits_{h\to0}\frac{h(-4x^3-6x^2h-4xh^2-h^3)}{hx^4(x+h)^4}=\lim\limits_{h\to0}\frac{-4x^3-6x^2h-4xh^2-h^3}{x^4(x+h)^4}\\\\=\frac{-4x^3-6x^2\cdot0-4x\cdot0^2-0^3}{x^4(x+0)^4}=\frac{-4x^3}{x^4\cdot x^4}=\frac{-4}{x^5}\\\\\\D_f=D_{f'}=\mathbb{R}\ \backslash\ \{0\}[/tex]
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We hope this was helpful. Please come back whenever you need more information or answers to your queries. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.